Toussaint Louverture : The Story of the Only Successful Slave Revolt in History; A Play in Three Acts - James, C. L. R. (Cyril Lionel Robert), 1901-1989 (Book collections on Project MUSE., 2013)
A new critical edition of Toussaint Louverture, the play written by the Trinidadian intellectual and activist C.L.R. James in 1934, performed at London's Westminster Theatre in 1936, and then presumed lost until its rediscovery in 2005.